Budowanie jakościowej przewagi konkurencyjnej wyrobów mleczarskich i jej znaczenie dla konsumentów - Góralczyk, Marzena (Building up of Competitive Quality of the Dairy Products and Its Importance for Consumers, 2005)
This article presents factors influencing the building up of competitiveness quality of dairy products according to the opinion of consumers and producers from Lubuskie province. It shows what the producers were doing in this area and presents some advice for the company of these food products in order to increase the competitiveness of their offer.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 277-283